EP.FRI.300 Equine related trauma: a 20-year district general hospital experience. (28th October 2021) - Dick, Lachlan; Yule, Michael; Green, James; Young, Jamie
Abstract: Introduction: Although a popular recreational and competitive sport, horse riding carries risk of injury. We aimed to characterise demographics, injury patterns and outcomes of patients with an equine-related injury over a 20-year period. Methods: Patients were identified through local coding. Data relevant to the study aims were extracted. Statistical analysis was used to determine any association between patient demographic with injury pattern or outcome. Results: Of the 701 patients included, 71.3% were female and the mean age was 34.9 years. Simple head injury (25.4%) and upper limb fracture (21.3%) were the commonest injuries. Abdominal visceral injury occurred in 1.6% with 2 patients requiring laparotomy and splenectomy. Overall, operations were performed in 32.8%. Open reduction and internal fixation was the commonest procedure (42.4%). 30-day mortality was 0.3% and 3.1% required transfer to a tertiary centre. Older patients were more likely to have a rib (46.3 vs 33.5 years, p = <0.05) or lower limb fracture (37.9 vs 34.5 years, p = 0.04) whilst upper limb fractures were seen in younger patients (30.3 vs 36.1 years, p = <0.05). There was no statistical difference with other injury patterns or gender. Conclusion: Although mortality is rare, a significant proportion of patients sustain injury requiring surgical intervention. Given the predisposition towards orthopaedic injury, adequate rehabilitation facilities need to be available. Continued development and promotion of safety equipment are also required to reduced incidence.